Pengembangan Media Pembelajaran Kosakata Bahasa Arab Berbasis Plotagon Story Di SMP Muhammadiyah 8 Tanggulangin Sidoarjo - Atika Rahmawati; Khizanatul Hikmah (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2022)
The more Arabic vocabulary mastered, the easier it is to use Arabic because it can convey meaning to other people well. The use of media affects the suitability of messages received by students. One of the media that can be used in learning Arabic vocabulary is an animated learning video based on the Plotagon Story application. In observations made at SMP Muhammadiyah 8 Tanggulangin Sidoarjo, researchers found a lack of innovation in learning Arabic, especially in Arabic Vocabulary. The development of Arabic vocabulary learning media based on the Plotagon Story application in schools aims to provide innovation in Arabic learning media so as to help students understand Arabic vocabulary. In this study, researchers used the R&D development research method with the Addie model and with research instruments in the form of interviews, observations, questionnaires which were then analyzed using descriptive (qualitative) and quantitative analysis techniques. The result of this research is that the cumulative percentage of student responses to the Plotagon Story application-based vocabulary learning media is 82.4%. Utilization of technology in learning media aims to add student learning styles, not limiting the time and place for students to study, providing space for students to use technology for education.